CHANGES IN SPINAL RANGE OF MOTION AFTER 16 WEEKS TRAINING PROGRAM IN PUBERTAL CHILDREN - Mónika Szigethy; Katalin Nagyváradi; Judit H. Ekler; Ferenc Ihász (University of Debrecen, Institute of Sport Sciences, 2021)
The aim of the present research was to improve the neglect behavior of pubertal children in an intervention program. Within the framework of the program, the main function of the spinal column and the strength and extensibility of the muscles responsible for posture were investigated. The participants included in the study are 7th grade children of the Neumann János Elementary School in Szombathely, Hungary, (nb=7); (ng=10). The Idiag M360 Spinal Mouse was used to investigate the physiological curvatures and main function of the spinal column before and after the program. The device was used to examine the children's spines in standing, bending forward and again in a standing position after the Matthiass test was performed. Pre-intervention (1) and post-intervention (2) data showed significant decreases in all assessed characteristics and similar increases in sacrum to hip ratio (Sac/Hip) (9.83±4.36 - 21.63±4.39); p<0.000.  The greatest change was found in the Th11/12 dorsal vertebral body angles (4.50±2.05 - -0.30±0.25); p<0.000. As a result of the postural improvement program, the degree of pelvic tilt and, in parallel, the physiological curvature of lumbar lordosis was reduced to within the age-specific reference values.